Genome‐wide association analysis of sucrose concentration in soybean (Glycine max L.) seed based on high‐throughput sequencing - Meinan Sui; Yue Wang; Yuyue Bao; Xi Wang; Ruiqiong Li; Yan Lv; Ming Yan; Chao Quan; Chunxia Li; Weili Teng; Wenbin Li; Xue Zhao; et al. (The Plant Genome, 2020)
Abstract The sucrose concentration in soybean seed significantly affects the flavor of soybean‐derived products. In this study, an association panel of 178 elite accessions and 33,149 single‐nucleotide polymorphisms (SNPs) was utilized to identify quantitative trait nucleotides (QTNs) of sucrose concentration in soybean seeds by genome‐wide association study (GWAS). Five QTNs (rs2688589, rs29026218, rs5926884, rs6886889, and rs10299216) distributed across five genomic regions in five chromosomes were identified in two or more locations by GWAS. A total of 60 candidate genes near the 200‐kb flanking region of these five identified loci were identified. Three of these genes (Glyma.04G032600, Glyma.04G034600, and Glyma.11G092100) have been reported to be involved in the process of sugar biosynthesis. Based on gene‐based association and haplotype analyses, a total of 35 SNPs from 10 genes associated with sucrose concentration were identified. Of them, Glyma.04G032600 was the only gene that has been reported to be related to sucrose content; the other nine genes were novel and may be associated with sucrose content. These beneficial alleles and candidate genes may be of great value in improving sucrose content in soybean seeds.